Cochrane Rapid Reviews Methods Group offers evidence-informed guidance to conduct rapid reviews (2020)
Objective: To develop methods guidance to support the conduct of rapid reviews (RRs) produced within Cochrane and beyond, in response to requests for timely evidence syntheses for decision-making purposes including urgent health issues of high priority. Study Design: Interim recommendations were informed by a scoping review of the underlying evidence, primary methods studies conducted, and a survey sent to 119 representatives from 20 Cochrane entities, who were asked to rate and rank RR methods across stages of review conduct. Discussions among those with expertise in RR methods further informed the list of recommendations with accompanying rationales provided. Results: Based on survey results from 63 respondents (53% response rate), 26 RR methods recommendations are presented for which there was a high or moderate level of agreement or scored highest in the absence of such agreement. Where possible, how recommendations align with Cochrane methods guidance for SRs is highlighted. Conclusion: The Cochrane Rapid Reviews Methods Group offers new, interim guidance to support the conduct of RRs. Because best practice is limited by the lack of currently available evidence for some RR methods shortcuts taken, this guidance will need to be updated as additional abbreviated methods are evaluated.